2020
DOI: 10.3389/fcell.2020.00339
|View full text |Cite
|
Sign up to set email alerts
|

Elevated suPAR Is an Independent Risk Marker for Incident Kidney Disease in Acute Medical Patients

Abstract: Introduction: Identifying patients at high risk of developing kidney disease could lead to early clinical interventions that prevent or slow disease progression. Soluble urokinase plasminogen activator receptor (suPAR) is an inflammatory biomarker thought to be involved in the pathogenesis and development of kidney disease. We aimed to determine whether elevated plasma suPAR measured at hospital admission is associated with incident kidney disease in patients presenting to the emergency department.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 42 publications
(50 reference statements)
1
24
0
Order By: Relevance
“…Patients with AKI exhibited significantly higher median plasma levels of suPAR and NGAL compared to patients without AKI ( Figure 1 ). Plasma suPAR and NGAL levels were also inversely correlated with baseline eGFR ( Figure A1 ), which supports previous literature demonstrating the connection between these biomarkers and kidney function [ 25 , 27 , 29 ]. The associations with suPAR may indicate the role of suPAR in systemic inflammation, which is expected to be elevated in our study group.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Patients with AKI exhibited significantly higher median plasma levels of suPAR and NGAL compared to patients without AKI ( Figure 1 ). Plasma suPAR and NGAL levels were also inversely correlated with baseline eGFR ( Figure A1 ), which supports previous literature demonstrating the connection between these biomarkers and kidney function [ 25 , 27 , 29 ]. The associations with suPAR may indicate the role of suPAR in systemic inflammation, which is expected to be elevated in our study group.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have suggested the systemic inflammatory biomarker soluble urokinase plasminogen activator receptor (suPAR) as an early biomarker for detection of AKI [ 25 , 26 , 27 , 28 , 29 ]. suPAR is a signaling glycoprotein thought to be involved in kidney disease pathogenesis [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we require more knowledge about which patients have the best effect of medication deprescribing in relation to readmission and mortality. Recent literature has shown that the use of soluble urokinase-type plasminogen activator receptor (suPAR), as a non-specific inflammatory marker is strongly associated with disease burden, disease progression, readmission, and mortality [ 38 , 39 , 40 , 41 , 42 ]. It would be of high scientific value to investigate the effect of a deprescribing intervention in patients with low, intermediate or high suPAR levels.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously shown that low suPAR is associated with low risk of adverse outcomes for acute medical patients, such as acute kidney injury (12,13 ), acute surgery ( 14), and overall mortality (10). These studies were mainly retrospective biobanked studies using ELISA platform for measurement of suPAR in batches, which demands manual work and has high processing time.…”
Section: Discussionmentioning
confidence: 99%